Galantamine protects against lipopolysaccharide-induced acute lung injury in rats - Li,G. (2016)
Lipopolysaccharide (LPS)-induced endotoxemia triggers the secretion of proinflammatory cytokines and can cause acute lung injury (ALI). The high mobility group box 1 (HMGB1) protein plays an important role as a late mediator of sepsis and ALI. Galantamine (GAL) is a central acetylcholinesterase inhibitor that inhibits the expression of HMGB1. This study evaluated the effects of GAL by measuring levels of inflammatory mediators and observing histopathological features associated with LPS-induced ALI. Sixty 8-10 week old male Sprague-Dawley rats (200-240 g) were randomized into three groups as follows: control group, LPS group (7.5 mg/kg LPS), and LPS+GAL group (5 mg/kg GAL before LPS administration). Histopathological examination of lung specimens obtained 12 h after LPS administration was performed to analyze changes in wet-to-dry (W/D) weight ratio, myeloperoxidase (MPO) activity, and HMGB1 expression level. Additionally, plasma concentrations of tumor necrosis factor-α, interleukin-6, and HMGB1 were measured using an enzyme-linked immunosorbent assay at 0 (baseline), 3, 6, 9, and 12 h after LPS administration. Mortality in the three groups was recorded at 72 h. LPS-induced ALI was characterized by distortion of pulmonary architecture and elevation of MPO activity, W/D weight ratio, and levels of pro-inflammatory cytokines, including tumor necrosis factor-α, interleukin-6, and HMGB1. Pretreatment with GAL significantly reduced the LPS-induced lung pathological changes, W/D weight ratio, levels of pro-inflammatory cytokines and MPO activity (ANOVA). Moreover, GAL treatment significantly decreased the mortality rate (ANOVA). In conclusion, we demonstrated that GAL exerted a protective effect on LPS-induced ALI in rats.